2015
DOI: 10.1136/bmjdrc-2014-000065
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a structured education program for children with diabetes: lessons learnt from an integrated process evaluation

Abstract: BackgroundThere is recognition of an urgent need for clinic-based interventions for young people with type 1 diabetes mellitus that improve glycemic control and quality of life. The Child and Adolescent Structured Competencies Approach to Diabetes Education (CASCADE) is a structured educational group program, using psychological techniques, delivered primarily by diabetes nurses. Composed of four modules, it is designed for children with poor diabetic control and their parents. A mixed methods process evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
1
20
1
Order By: Relevance
“…The present study is unique, as earlier educational program in adolescents have not been able to demonstrate improvement in glycaemic control for either boys or girls . In the present study, the intervention had an effect on boys' glycaemic control.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The present study is unique, as earlier educational program in adolescents have not been able to demonstrate improvement in glycaemic control for either boys or girls . In the present study, the intervention had an effect on boys' glycaemic control.…”
Section: Discussioncontrasting
confidence: 54%
“…Attendance was high in the study, an aspect that was found to be difficult in a previous study . Usually, families experience the initiation of CSII as a positive event, and it can thus be easier to achieve higher attendance as the study has a connection with other positive changes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Offering creative educational approaches that include a strong psychosocial support aspect could be a cost-effective and patient-centered approach. 51 This pilot-level observational study illustrates the feasibility of assessing QOC where little data have been collected-among rural American youth with T1DM. Future studies should consider the unique needs of rural patients with diabetes in intervention efforts focused on serving, educating or delivering tailored diabetes care to reduce disparities between urban and rural residents.…”
Section: Discussionmentioning
confidence: 91%
“…Between 28 July 2014 and 9 December 2014, 89 eligible families (44% females; mean age 12.4 years, range [8][9][10][11][12][13][14][15][16] received study information, either prior to attending or during their clinic appointment. They were then approached to take part during clinic or were called on the telephone.…”
Section: Recruitmentmentioning
confidence: 99%